Peran Sitokin dalam Patogenesis Berbagai Kelainan Mukosa Mulut (Tinjauan Pustaka) - Niniarty Z. Djamal; Endang Winiati (Faculty of Dentistry, Universitas Indonesia, 2015)
Cytokines are polypeptide growth factors and produced by most nucleated cells in the body. The Homeostatic mechanism in oral mucosa is affected by these factors, which are produced by immunocompetent or un immunocompetent cells in the oral mucosa. Cytokine has more than one function and activity, that is called "pleiotropic", and if wokres in sinergishc and anatgonistic system. According to the function there are 6 kindo of cytokines as follows: Interleukin (IL), tumor necrosis factor (TNF), Kemokin, Collony Stimulating factor (CSF), Interferon (IFN) and growth factor (GF). Many agents will invade oral mucosa and will produce unstable cytokine, therefore: this situation can cause pathologic condition in oral mucosa such as lichen planus, autoimmune disease and neoplasma.